The "Pots and Pans" protests and requirements for responsiveness of the authorities - Önnudóttir, Eva H. (Stjórnsýslustofnun, 2016)
This paper examines under what conditions it is justifiable that the government takes into account the demands of protesters and whether the terms of procedural-equality in protest participation were met in the ‘Pots and Pans’ protests in Iceland in 2008–09. The protests were triggered by a financial melt-down in Iceland and did not come to an end until almost all the main demands of the protesters had been met. The main conclusion is that due to the seriousness of the issues which triggered the protests and that those issues were of national concern, together with the large numbers of protesters and wide support for their demands as well as extensive public discussion about the issues of the protests, they were a prime example of a situation when the authorities should consider taking the demands of protesters into account. Furthermore, in this paper it is established that giving in to the demands of the protesters was within the terms of procedural-equality between the protesters and those who did not participate – adding to the justification that, in this case, it was justifiable to defer to the protesters’ demands.